FESTIVAL OGOH-OGOH : DAMPAK EKONOMI DAN PROMOSI PARIWISATA DAERAH KOTA MATARAM - Ida Wayan Demung (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2026)
The Ogoh-Ogoh festival in Mataram City has. Evolved from a purely Hindu religious ritual into a cultural phenomenon that attract widespread attention. Yhis study aims to analyze the economic impact and the effectiveness of the festifval as aregional promotion tool within the framework of culture-based tourism. Using a descriptive qualitative method with a case study approach data were collected through field obeservations, document studies and in-depth interviews with stakeholders. The results indicate that the Ogoh-Ogoh Festival provides a significant economic impact by increasing local MSME activities, hotel occupancy rates and transportation services around the city center. Furthemore, the festival serves as an affective regional promotion instrument, strengthening Mataram’s image as an inclusive and relius cultural destination. However, the study also notes the need for more integratued event management to address logitical contraints an mantain the sustainability of the tradition amidst commercializattion.